Postoperative cerebrospinal fluid leak after microvascular reconstruction of craniofacial defects with orbital exenteration. (7th September 2016) - Gill, Kurren S.; Hsu, David; Tassone, Patrick; Pluta, John; Nyquist, Gurston; Krein, Howard; Bilyk, Jurij; Murchison, Ann P.; Iloreta, Alfred; Evans, James J.; Heffelfinger, Ryan N.; Curry, Joseph M.
Abstract : Objectives: To assess risk factors for cerebrospinal fluid (CSF) leak and complications after microvascular reconstruction of cranio‐orbitofacial resection with orbital exenteration (CFOE). Study Design: Retrospective case series. Methods: Seventy consecutive patients at a tertiary hospital underwent 76 procedures with microvascular reconstruction of CFOE defects. Patients were stratified by extent of skull base exposure and presence or absence of dural resection. Patients with exposure of the orbital apex and roof alone were classified as minimal skull base exposure (MS) (n = 32). Those with skull base exposure beyond the orbital apex and roof were classified as significant skull base exposure (SS) (n = 38) and were subdivided into those with dural exposure (SSe) (n = 15) and those with dural resection (SSr) (n = 23). The main outcome measure was incidence of postoperative CSF leak according to univariate and multivariate analysis of risk factors, including previous radiation, surgery, and location of defect. Results: Intraoperative leaks occurred in five and four patients in the MS and SSe groups, respectively, with no postoperative leaks. In the SSr group, five patients developed a postoperative CSF leak and three required operative management. Multivariate analysis revealed middle fossa exposure to be the only significant predictor of CSF leak ( P = 0.03). The overall complication rate was 31.6%. Major complications were greater in the SS group compared to the MS group ( P = 0.05). Conclusion: In this series, middle fossa resection increased the risk of postoperative CSF leak after microvascular reconstruction of CFOE defects, and complication rates were greater with more complex defects. Level of Evidence: 4. Laryngoscope, 127:835–841, 2017